Iron-group abundances in the metal-poor main-sequence turnoff star HD 84937 - Sneden, Christopher; Cowan, John J.; Kobayashi, Chiaki; Pignatari, Marco; Lawler, James E.; Den Hartog, Elizabeth A.; Wood, Michael P. (Astrophysical journal, 2016)
We have derived new, very accurate abundances of the Fe-group elements Sc through Zn (Z = 21−30) in the bright main-sequence turnoff star HD 84937 based on high-resolution spectra covering the visible and ultraviolet spectral regions. New or recent laboratory transition data for 14 species of seven elements have been used. Abundances from more than 600 lines of non-Fe species have been combined with about 550 Fe lines in HD 84937 to yield abundance ratios of high precision. The abundances have been determined from both neutral and ionized transitions, which generally are in agreement with each other. We find no substantial departures from the standard LTE Saha ionization balance in this [Fe/H] = −2.32 star. Noteworthy among the abundances are [Co/Fe] = +0.14 and [Cu/Fe] = −0.83, in agreement with past studies of abundance trends in this and other low-metallicity stars, and <[Sc,Ti,V/Fe]> = +0.31 which has not been noted previously. A detailed examination of scandium, titanium, and vanadium abundances in large-sample spectroscopic surveys reveals that they are positively correlated in stars with [Fe/H] < −2; HD 84937 lies at the high end of this correlation. These trends constrain the synthesis mechanisms of Fe-group elements. We also examine the Galactic chemical evolution abundance trends of the Fe-group elements, including a new nucleosynthesis model with jet-like explosion effects.
Keywords: Atomic data; Galaxy: evolution; Nuclear reactions; nucleosynthesis; abundances; Stars: abundances; Stars: individual (HD 84937); Stars: population II